Adult learners need a variety of pathways to completion. Issue 8 (26th March 2019) - Sutton, Halley
Abstract : Sylvia Burgess, associate vice president of academic affairs at Cameron University, wears a lot of hats. Not only is she the associate vice president of academic affairs, but she also acts as the director for continuing and adult education at CU. Like many adult‐serving institutions, CU offers both live and asynchronous courses, and it also offers remote adult learners a third option: the option to stream and interact with faculty members from a remote location via the Zoom webinar platform. It's become a way for adult students who might have moved away or not yet completed their studies to stay connected with the university, Burgess said.